Sex-specific effect of P2Y2 purinergic receptor on glucose metabolism during acute inflammation - Ulbricht, Randi J.; Rivas, Christian A.; Marino, Hailee; Snyder, Erin; James, Dana; Makhloufi, Jamila; Johnson, Nathan; Zimmerman, Scott; Wang, Jianjie (Frontiers in Endocrinology, 2023)
The sex of an animal impacts glucose sensitivity, but little information is available regarding the mechanisms causing that difference, especially during acute inflammation. We examined sex-specific differences in the role of the P2Y2 receptor (P2Y2R) in glucose flux with and without LPS challenge. Male and female wild-type and P2Y2R knockout mice (P2Y2R-/-) were injected with LPS or saline and glucose tolerance tests (GTT) were performed. P2Y2R and GLUT4 transporter gene expression was also evaluated. Female mice had reduced fasting plasma glucose and females had reduced glucose excursion times compared to male mice during GTT. P2Y2R-/- males had significantly decreased glucose flux throughout the GTT as compared to all female mice. Acute inflammation reduced fasting plasma glucose and the GTT area under the curve in both sexes. While both wild-type and P2Y2R-/- male animals displayed reduced fasting glucose in LPS treatment, female P2Y2R-/- mice did not have a statistically significant change in fasting glucose between LPS and saline treatments, suggesting that the effects of P2Y2R are specific to male mice, even under inflammatory conditions. Overall, we conclude that the role for the purinergic receptor, P2Y2R, in regulating glucose metabolism is minimal in females but plays a large role in male mice, particularly in the acute inflammatory state.